Technologies enabled in the 4.0 industry: opportunities and challenges of application in financial management (Research, Society and Development, 2022)
Financial indices are extremely important for companies, and a factor of attention, since they correspond to essential aspects, which are linked to investments and monetary values, fundamental for the existence of any business. Financial performance indicators refer to data collected related to payments, investments, sales and equipment that the company has, and are related to cash, inventories, outstanding debts, costs with resources and raw materials. To manage a company's finances in the best way, strategic planning, reliable data, good supplier relationships, and investment management are required. This study, through a literature review, sought to identify the main key financial performance indicators (KPI's) that can be improved with the support of enabling technologies from industry 4.0, verifying whether these technologies can represent an opportunity or a challenge for each KPI. It can be seen that the financial indicators are not strictly linked to the calculations, normally studied in many analyses, but they have the potential for study and exploration by other tools, and with that the company's equity and capital can be safer, and the deadlines can be fulfilled. It was also noted that the search for an increase in revenue, reduction of risks and losses, generates a huge concern, but does not necessarily need to be an obstacle.